Government and village commitment to support GERCEPS action of youth caring movement for stunting in Sampang - Fauziah, Nuraini; Fa’ni, Renidya Asyura Muttabi’ Deya; Rosanti , Nadia Dian; Pujiyani, Honesty; Ferdina, Cucun Setya; Putri , Nindi Pramesthi Vardila; Raharja, Kristian Triatmaja; Syakura, Abdan; Mustofa , Ahmad (Universitas Ahmad Dahlan, 2024)
Stunting is a health problem caused by a chronic lack of intake of both macro and micronutrients, which results in irreversible growth and development in children. Child health efforts are carried out for fetuses, newborns, infants, toddlers, preschoolers, school-age children, and teenagers. The existence of teenagers is one of the global policies focused on SDGs. However, anemia impact can give birth to babies whose development is not optimal. Peer involvement is needed in optimizing education on stunting and anemia prevention movements. GERCEPS is a youth posyandu innovation based on stunting reduction, as a pilot project in Sampang district, an acronym for Youth Movement to Prevent and Care for Stunting. This research aims to understand the government and village commitment to supporting GERCEPS action in Sampang. This research was a descriptive qualitative design using primary data sources through in-depth interviews and participant observation. The sampling technique was purposive sampling of 9 informants in 12 stunting locus villages in Sampang. Informants’ criteria for this research are residents in Sampang Regency who have work and positions in government and the village. The question instrument refers to Allen & Meyers's theory with modifications. Narrative analysis technique. The results showed that Sampang Regency had demonstrated commitment and support for the GERCEPS action effectively, sustainably, and normatively. The penta-helix approach strengthens the role of local government. However, the village character in GERCEPS action is not yet optimal because this activity is a new program and still requires adaptation and consistency. This research showed that the implications of good commitment can result in good actions at every level to reduce stunting. We hoped that the government would more optimally provide the best support to the village in implementing GERCEPS, especially ongoing training for village officials and youth cadres in implementing the GERCEPS action youth posyandu